The middle-income trap 2.0 - Glawe, Linda,Wagner, Helmut (Center for East Asia Macro-Economic Studies, University of Hagen, 2020)
We modify the concept of the middle-income trap (MIT) against the background of the Fourth Industrial Revolution and the (future) challenges of automation (creating the concept of the
urn:nbn:de:hbz:708-dh9608
Keywords: Graue Literatur; automation; AI; human capital; middle-income trap; developing Asia; economic development; economic growth; employment